Integrating Culturally Responsive Teaching and Role-Playing to Enhance Biology Learning Motivation - Tuapattinaya, Prelly Marsel Jolanda; Pradana, Sendy Putra (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2025)
This classroom action research was conducted in 2024 at SMA Negeri 42 Maluku Tengah, specifically in grade X Biology, focusing on the Plantae topic. The study was motivated by the low student engagement and learning outcomes, which were evident from several factors, including lack of enthusiasm during lessons, minimal participation in learning activities, the perceived irrelevance of the material to daily life, and overall poor academic performance. To address these issues, a combination of the Culturally Responsive Teaching (CRT) approach and the Role Playing model was implemented. This strategy aimed to enhance students' comprehension by connecting the material to real-world experiences, thereby improving their academic performance. Conducted in two cycles, the study revealed a significant improvement, with student motivation reaching 98% and learning outcomes achieving 100%. Students with higher motivation demonstrated better academic results as they were actively engaged in the learning process and could relate the material to their everyday experiences. The findings suggest that integrating the Culturally Responsive Teaching (CRT) approach with the Role Playing model effectively enhances student motivation and learning outcomes in Biology, particularly in the Plantae topic.